0080 Leptin Induces Upregulation Of The Hypoxic Ventilatory Response Acting In The Carotid Bodies. (27th April 2018) - Caballero Eraso, C; Shin, M; Pho, H; Schwartz, A; Tang, W; Sham, J; Polotsky, V
Abstract: Introduction: Obesity leads to an increase in the hypoxic ventilatory response (HVR), which is controlled by the carotid bodies (CBs). Mechanisms of the increased HVR in obesity are unknown, but leptin may play a role. We hypothesized that hyperleptinemia increases the CB chemoreflex leading to increased HVR and respiratory instability during sleep. Methods: 1 ) Male C57BL/6J wild type mice (WT) were exposed to room air and 10% O2 +3% CO2 . Minute ventilation (VE ) and HVR (the slope of the relationship between the change in O2 saturation (ΔSpO2 ) and the change in minute ventilation (ΔVE )) were measured at baseline and during subcutaneous leptin infusion (120 µg/day for 3 days). Subsequently, CSN denervation (CSND) was performed and the measurements were repeated. 2 ) We developed a novel technique to express an ObRb leptin receptor (LepR) in LepR deficient db/db mice CB using an adenoviral vector suspended in Matrigel. HVR and VE were measured at baseline and after expression of LepR gene or luciferase (control). 3 ) Sleep studies and arterial blood gas (ABG) measurements were performed in db/db mice after gene transfection. The oxygen desaturation index (ODI) and VE were measured during sleep Results: 1 ) In WT mice, leptin increased HVR from 2.03 ± 0.19 ml/min*Δ%O2 to 2.73 ± 0.16 ml/min*Δ%O2, p=0.028 and this effect was attenuated after CSND (2.96 ± 0.24 ml/min*Δ%O2 vs 1.80 ± 0.17 ml/min*Δ%O2, p=0.001) 2) LepR expression in CB of db/db mice also increased HVR (2.89 ± 0.18 vs 3.54 ± 0.42, p=0.03), whereas control virus had no effect (2.68 ± 0.14 vs 2.74 ± 0.3, p=0.8). 3) LepR expression in CB increased VE during NREM sleep (0.42 ± 0.03 ml/min/g vs 0.33 ± 0.01 ml/min/g after control virus, p=0.02). There was no effect of LepR on ODI. In addition, LepR transfection resolved baseline hypercapnia in ABG with PaCO2 decreasing to 39 ± 2 mm Hg vs 49 ± 4 in luciferase control (p=0.051). Conclusion: Leptin increases HVR. Leptin's effect on the HVR may occur in the CB. Leptin signaling in the CB may be protective against obesity hypoventilation, but there was no effect on OSA. Support (If Any): HL133100. HL138932